2020
DOI: 10.1111/asj.13464
|View full text |Cite
|
Sign up to set email alerts
|

The bio‐surfactant mannosylerythritol lipid acts as a selective antibacterial agent to modulate rumen fermentation

Abstract: Methyl-mannosylerythritol lipid (MEL), a new sugar esterified lipid synthesized by Pseudozyma aphidis, was assessed for its functionality in modulating rumen fermentation and microbiota toward more propionate and less methane production. A pure culture study using rumen representatives showed that MEL selectively inhibited the How to cite this article: Okuhira K, Koike S, Ito S, Kobayashi Y. The bio-surfactant mannosylerythritol lipid acts as a selective antibacterial agent to modulate rumen fermentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Similarly, the growth of gram-positive bacteria (Bacillus megaterium and Bacillus subtilis) was restrained by MEL-A and MEL-B reported by Recke et al, and they also found MELs showed moderate antifungal effects on Candida magnoliae [73]. Besides, Okuhira et al compared the antimicrobial effects of MEL against two types of bacteria and summarized MEL selectively inhibited the proliferation of most gram-positive bacteria below the concentration of 50 µg/mL, but not gram-negative bacteria [74]. Furthermore, Nashida et al synthesized 20 congeners of MELs through a chemical process and compared their inhibition on microbes, and the results illustrated not only the length of the alkyl chains but also the pattern of Ac groups on the mannose moiety were important factors for antibacterial activity [75].…”
Section: Tobacillus Caseimentioning
confidence: 92%
“…Similarly, the growth of gram-positive bacteria (Bacillus megaterium and Bacillus subtilis) was restrained by MEL-A and MEL-B reported by Recke et al, and they also found MELs showed moderate antifungal effects on Candida magnoliae [73]. Besides, Okuhira et al compared the antimicrobial effects of MEL against two types of bacteria and summarized MEL selectively inhibited the proliferation of most gram-positive bacteria below the concentration of 50 µg/mL, but not gram-negative bacteria [74]. Furthermore, Nashida et al synthesized 20 congeners of MELs through a chemical process and compared their inhibition on microbes, and the results illustrated not only the length of the alkyl chains but also the pattern of Ac groups on the mannose moiety were important factors for antibacterial activity [75].…”
Section: Tobacillus Caseimentioning
confidence: 92%
“…Surfactant not only influence the rumen metabolites but have impact on rumen microflora. For example, a recent study has demonstrated that the biosurfactant manosylerythritol lipid decrease the numbers of most of ruminal gram-positive bacteria, reduce methane production, and increase the ratio of propionate to acetate [ 10 ]. Our previous studies have extensively explored the anionic surfactant docusate (DOC or aerosol OT), an anionic surfactant, led to a in the diet decreased protozoan count, increased total amount of bacteria in rumen [ 11 ], increased activities of fiber-degrading enzymes in the rumen [ 12 ], increased nutrient absorption from the small intestine [ 9 ] and nitrogen retention in sheep [ 13 , 14 ], and improved the slaughter performance of lambs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%